Accommodation Management Perspectives Towards Green Program Implementation at Baturiti District, Tabanan Residence, Bali - Ni Desak Made Santi Diwyarthi (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
This research reveals the perspective of accommodation management regarding the implementation of green programs. The study involved 10 accommodation managements at Baturiti District, Tabanan Residence, Bali. The research used a survey approach, incorporating interviews, questionnaires, and observations. The conclusion of the study is that the accommodation managements in Tabanan believe that green programs need to be implemented because their accommodation are environmentally friendly, can be a business attraction, and are energy-efficient.